The CAPRISA Clinical Trials: HIV Treatment and Prevention - Abdool Karim, Quarraisha; Abdool Karim, Salim S.; Baxter, Cheryl (Springer International Publishing : Imprint: Springer, 2017)
Since its inception 14 years ago, CAPRISA has conducted numerous clinical studies that have influenced international TB-HIV treatment guidelines as well as HIV prevention through innovations in the microbicide and vaccine fields. This book provides a historical account of how each of CAPRISA's high impact studies was created, developed, implemented, analysed and communicated. In doing so, the reader is taken on a journey that provides glimpses into the genesis of research ideas and how this ultimately leads to a range of HIV prevention and treatment studies that have impacted the global response to the HIV and TB epidemics. Comprised of 5 sections, the book details the following: HIV epidemic in South Africa and the establishment of a research centre to undertake clinical, epidemiological and laboratory research on HIV. CAPRISA's clinical trials on HIV and HSV-2 prevention. These studies investigated the impact of tenofovir gel as topical antiretroviral pre-exposure prophylaxis (PrEP), implementation of topical PrEP through family planning clinics, conditional cash incentives for HIV prevention, HIV vaccines, and passive immunisation with broadly neutralising antibodies. CAPRISA's research on the treatment of HIV and TB co-infection. A review of the major scientific findings from the CAPRISA studies on acute infection and genital mucosal immunology. Essential support activities for the conduct of clinical trials, including research laboratories and pharmacies, as well as establishing effective communication and sustainable structures for community engagement to maintain effective and respectful partnerships with participating communities. The book concludes with a chapter about the challenges facing future HIV prevention and treatment trials. The CAPRISA Clinical Trials: HIV Treatment and Prevention is a resource for undergraduate and postgraduate students, health care providers, doctors, decision-makers and researchers who are seeking guidance and insights on clinical trials - their creation, conduct and impact.
Keywords: Medicine.; Health promotion.; Health informatics.; Infectious diseases.; elektronické knihy; electronic books